Ancient Magreben Poetry and the problematical Issue of Imitation and Innovation A study of the Poet Iben Kadi Mila’s Madripal Poem - BOUZIDI, SALLIME (Milev Journal of Research and Studies, 2016)
Iben Kadi Mila is one of the superbly gifted Magreben poets. He is the proprietor of an outstanding school of poetry. He is mostly renowned for his contributions in developing Arabic poetry at the linguistic and stylistic levels. Notwithstanding his scarce poetic products, which are dispersed in a few literary and historical resources, his laudably matchless praises of Thiquat Eddawla Iben Elkalbi is a prototype of well-developed Maghrebian poetry. He knew through it how to take full advantage of the Eastern poetic school and craft thereafter his own peculiar poetic style.